Analysis of the Level of Understanding of Handling, Prevention, and Treatment of Ankle Injuries in Extracurricular Volleyball Students - Rumpoko, Satrio Sakti; Sistiasih, Vera Septi; Sunjoyo, Sunjoyo; Sholeh, Muchammad; Suarez, Neriza (Journal Coaching Education Sports, 2024)
Extracurricular volleyball at SMKN 2 Pacitan often experiences injuries, both during practice and matches. Lack of attention to the risk of injury results in players having a limited understanding of injury management, leading them to seek alternative treatments without specific care. This quantitative, descriptive research aims to assess players' knowledge of the risks, prevention, and treatment of ankle injuries. The research population includes 30 students participating in extracurricular volleyball at SMKN 2 Pacitan. Data is collected through a questionnaire, and the analysis using the Likert scale is performed to identify players' understanding of injuries. The results indicate that the level of understanding of the first aid, prevention, and treatment of ankle injuries in extracurricular volleyball students at SMKN 2 Pacitan falls into the "strong" category with a percentage of 83%, "very strong" at 3%, while the "fair" category is at 13%. The novelty of this research lies in its in-depth focus on students' perceptions of various aspects addressed in the questionnaire and how this insight can contribute to the development of methods or policies in the future.